MAPPING AND IMPLEMENTING COMPLEXITY-BASED STRATEGIES IN ISLAMIC EDUCATION MANAGEMENT TO OPTIMIZE THE DYNAMIC INTERACTION BETWEEN TEACHERS AND STUDENTS IN THE LEARNING PROCESS - Muhammad Ihsan Dacholfany (Adisam Publisher, 2023)
This research, titled